Pendampingan Menghafal Al-Qur’an dengan Menggunakan Metode Ummi di Pengajian Qurrata A’yun - Adisa Riski Bumi; Dede Supendi (PT. Bangun Harapan Bangsa, 2023)
The Qurrata A'yun recitation, which is located in the Bukit Berbunga Housing Complex, Mekargalih Village, Purwakarta Regency, is a place for learning the Koran. Lack of ability to understand the Qur'an, especially reading according to the rules and remembering it is the concern and focus of devotion. Lack of ability to read the Qur'an, as well as the learning process that takes time, also causes a lack of concentration when studying it. The verses of the Qur'an contain a wide range of words, making it difficult to read fluently. This is one of the obstacles for reading and memorizing the Qur'an. This problem stems from a lack of understanding of tajwid which is often taught practically, forcing children to memorize it. The aim of this activity is to teach children how to read and remember the Quran in such a way that their reading conforms to the guidelines. The approach used in the mentoring is face-to-face teaching of the Qur'an to children who read the Qur'an using the Ummi technique. After the mentoring, the participants' ability to read and memorize the Qur'an changed and improved.